Fundamentals of developing students’ cognitive abilities in european universities - Dolishnia, N.; Mahanova, T. V.; Botuzova, Yu.; Moisieieva, N.; Tsybulska, T. Ye.; Маганова, Тамара Валеріївна; Цибульська, Таміла Євгенівна (My University, 2023)
The purpose of the academic paper is to study the fundamentals of developing students’ cognitive abilities in European universities. The methodology included a subject study to describe the fundamentals of developing students’ cognitive abilities based on analyzing secondary data and materials of the European Commission, the analysis of the cases of European universities’ two alliances: The 4EU+ European University Alliance (2023a) and The Arqus European University Alliance (2023a). The results indicate the development of quality inclusive education in the EU based on common human values and a partnership approach to cooperation between institutions and communities.
Mahanova T. V. - https://orcid.org/0000-0001-7008-3102; Tsybulska T. Ye. - https://orcid.org/0000-0002-1745-7002
Keywords: cognitive abilities; European universities; European educational space; EU’s competence framework